A secreted helminth microRNA suppresses gastrointestinal cell differentiation required for innate immunity - Perez, Matias G.; Gillan, Victoria; Anderson, William M.; Gerbe, François; Herbert, Fabien; McNeilly, Tom N.; Maizels, Rick M.; Jay, Philippe; Devaney, Eileen; Britton, Collette (Frontiers in Immunology, 2025)
Pathogens have developed multiple strategies to modulate host immune defense mechanisms. Understanding how this is achieved has potential to inform novel therapeutics for diseases caused by immune dysfunction. Parasitic helminths are masters of immune evasion, via release of secreted products, resulting in chronic infection. Helminths secrete small regulatory microRNA (miRNAs), which can interact with host cells. Here we show that a single parasite miRNA (miR-5352), conserved across gastrointestinal (GI) nematodes, suppresses IL-13-induced GI epithelial cell differentiation and cytokine responses, and promotes stem cell maintenance. Mechanistically, this is achieved through targeted repression of critical host factors, including Klf-4 and the IL-22 receptor, together with modulation of Wnt and Notch signalling pathways. Nematode miR-5352 shows seed sequence conservation with mammalian miR-92a family members, indicating that through convergent evolution, GI nematodes exploit a host miRNA regulatory network to suppress host innate responses, promote tissue regeneration and establish a favourable environment for chronic infection.